Binding of a Ruthenium Complex to a Thioether Ligand Embedded in a Negatively Charged Lipid Bilayer: A Two‐Step Mechanism. Issue 24 (29th April 2014) - Bahreman, Azadeh; Rabe, Martin; Kros, Alexander; Bruylants, Gilles; Bonnet, Sylvestre
Abstract The interaction between the ruthenium polypyridyl complex [Ru(terpy)(dcbpy)(H2O)]2+ (terpy=2, 2′;6′, 2"‐terpyridine, dcbpy=6, 6′‐dichloro‐2, 2′‐bipyridine) and phospholipid membranes containing either thioether ligands or cholesterol were investigated using UV–visible spectroscopy, Langmuir–Blodgett monolayer surface pressure measurements, and isothermal titration calorimety (ITC). When embedded in a membrane, the thioether ligand coordinated to the dicationic metal complex only when the phospholipids of the membrane were negatively charged, that is, in the presence of attractive electrostatic interaction. In such a case coordination is much faster than in homogeneous conditions. A two‐step model for the coordination of the metal complex to the membrane‐embedded sulfur ligand is proposed, in which adsorption of the complex to the negative surface of the monolayers or bilayers occurs within minutes, whereas formation of the coordination bond between the surface‐bound metal complex and ligand takes hours. Finally, adsorption of the aqua complex to the membrane is driven by entropy. It does not involve insertion of the metal complex into the hydrophobic lipid layer, but rather simple electrostatic adsorption at the water–bilayer interface.